Language Teaching Techniques at Primary Level in Urban and Rural Areas - S. , Srinivas (International Journal of Psychosocial Rehabilitation, 2020)
English language instructing and learning is still particularly trying for the educators’ and understudies’ in Hyderabad. This paper shows the similar investigation of how the sentence structure educating methods impact in provincial and urban ESL study hall. The scientist directed the investigation on haphazardly chose 75 understudies and 6 educators of 8 ESL study halls at the essential level in the both urban and country regions of Bangladesh. Likert scale as been utilized to gather the information from the members. Quantitative strategy for investigation has been applied by the analyst with shows that instructors of urban and country territories vary in language structure educating strategies. This paper will have significant job in controlling instructors to utilize distinctive training methods to empowers language learning in the two zones.